2015
DOI: 10.1002/celc.201500094
|View full text |Cite
|
Sign up to set email alerts
|

High‐Temperature Electrochemistry of a Solvent‐Free Myoglobin Melt

Abstract: The electrochemical responses from a hybrid biofluid comprising lithium hexafluorophosphate (LiPF6) dispersed in a solvent‐free myoglobin melt are investigated over an extreme temperature range (30–150 °C). Incorporation of LiPF6 resulted in an approximately 20‐fold increase in the conductivity of the biofluid across the entire temperature range. A polaron‐type mechanism involving electron hopping from heme‐to‐heme centers of myoglobin, accompanied by extrinsic Li counter‐ion movement, is proposed for the char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…In this paper, we report a novel, generic, and facile method for fabricating protein‐sequestered LC droplets based on the sequestration of surface‐engineered protein–polymer surfactant (PS; poly(ethylene glycol) 4‐nonyl phenyl 3‐sulfopropyl ether potassium salt; M n = 1200) bioconjugates. The PS nanobioconjugates were prepared by electrostatic conjugation of an anionic PS to the surface of the cationized proteins (see Methods in the Supporting Information) . We show that mixing an aqueous solution of the core–shell PS bioconjugates with an aqueous dispersion of 4‐cyano‐4′‐pentylbiphenyl (5CB) nematic LC emulsion droplets results in biomolecule sequestration onto the droplet surface or into the LC interior without protein degradation or structural disruption of the 5CB matrix.…”
Section: Introductionsupporting
confidence: 94%
See 2 more Smart Citations
“…In this paper, we report a novel, generic, and facile method for fabricating protein‐sequestered LC droplets based on the sequestration of surface‐engineered protein–polymer surfactant (PS; poly(ethylene glycol) 4‐nonyl phenyl 3‐sulfopropyl ether potassium salt; M n = 1200) bioconjugates. The PS nanobioconjugates were prepared by electrostatic conjugation of an anionic PS to the surface of the cationized proteins (see Methods in the Supporting Information) . We show that mixing an aqueous solution of the core–shell PS bioconjugates with an aqueous dispersion of 4‐cyano‐4′‐pentylbiphenyl (5CB) nematic LC emulsion droplets results in biomolecule sequestration onto the droplet surface or into the LC interior without protein degradation or structural disruption of the 5CB matrix.…”
Section: Introductionsupporting
confidence: 94%
“…Preparation of Protein–Polymer Surfactant Nanobioconjugates : Preparation of nanobioconjugates of Mb and BSA was carried out via protein surface engineering with polymer surfactant by slight modification of the procedure reported in literature . Briefly, the surface engineering was performed in three steps as shown in Figure b (specifically demonstrated for Mb; for BSA see Supporting Information), and explained as follows:Labeling of Mb or BSA proteins with dyes: RITC (R) and FITC (F) tags were used to image multiple proteins in the LC droplets.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…27 (a) Molecular model of the Mb–surfactant complex. (b) Diagram of the three electrode cell configuration.…”
Section: Design Preparation and Application Of Biomacromolecular LImentioning
confidence: 99%
“…5 Recently, it was shown that a Mb melt deposited onto highly oriented pyrolytic graphite (HOPG) showed quasi-reversible electrochemical behaviour, 6 and similar behaviour was exhibited up to 150°C on a gold electrode. 7 Little knowledge has been gathered about the redox properties of the protein prior to the lyophilisation step, which could provide information about changes in the environment near the heme. Indeed, the formal reduction potential of the heme is rather sensitive to its chemical environment, which has been a source of controversy in the literature.…”
Section: Introductionmentioning
confidence: 99%